2016
DOI: 10.1016/j.celrep.2016.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Hypofunctional TrkA Accounts for the Absence of Pain Sensitization in the African Naked Mole-Rat

Abstract: SummaryThe naked mole-rat is a subterranean rodent lacking several pain behaviors found in humans, rats, and mice. For example, nerve growth factor (NGF), an important mediator of pain sensitization, fails to produce thermal hyperalgesia in naked mole-rats. The sensitization of capsaicin-sensitive TRPV1 ion channels is necessary for NGF-induced hyperalgesia, but naked mole-rats have fully functional TRPV1 channels. We show that exposing isolated naked mole-rat nociceptors to NGF does not sensitize TRPV1. Howev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 72 publications
(104 reference statements)
0
61
0
6
Order By: Relevance
“…18 Furthermore, response to low pH has been shown to be sensitized by inflammatory mediators. [19][20][21][22][23][24] We and others have demonstrated expression and function of TRPV1 and ASICs within articular sensory neurones, [25][26][27] and both TRPV1 and ASIC3 are upregulated in different inflammatory models, suggesting their involvement in inflammatory pain. 26,28,29 A common model for inflammatory arthritis involves intraplantar/intraarticular injection of complete Freund's adjuvant (CFA), 30 which although not replicating autoimmunity does provide a robust model of RA-like arthritis: T cell-mediated pathogenesis, leukocyte invasion, synoviocyte hyperplasia, pannus formation and disrupted gait.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…18 Furthermore, response to low pH has been shown to be sensitized by inflammatory mediators. [19][20][21][22][23][24] We and others have demonstrated expression and function of TRPV1 and ASICs within articular sensory neurones, [25][26][27] and both TRPV1 and ASIC3 are upregulated in different inflammatory models, suggesting their involvement in inflammatory pain. 26,28,29 A common model for inflammatory arthritis involves intraplantar/intraarticular injection of complete Freund's adjuvant (CFA), 30 which although not replicating autoimmunity does provide a robust model of RA-like arthritis: T cell-mediated pathogenesis, leukocyte invasion, synoviocyte hyperplasia, pannus formation and disrupted gait.…”
mentioning
confidence: 90%
“…Sensory neurones express several acid sensors: acid‐sensing ion channels (ASICs), transient receptor potential vanilloid 1 (TRPV1), proton‐sensing GPCRs and certain background K + channels 18. Furthermore, response to low pH has been shown to be sensitized by inflammatory mediators 19, 20, 21, 22, 23, 24…”
Section: Introductionmentioning
confidence: 99%
“…In the peripheral nervous system, ASICs are expressed by sensory neurons of the dorsal root ganglia (DRG) [13–16] and are involved in nociception and mechanosensation [17, 18]. Interestingly, the naked mole-rat ( Heterocephalus glaber ) shows no nocifensive response to acid due to a lack of activation of cutaneous sensory neurons [19], even though DRG neurons have ASIC-like currents and cloned ASIC1a and ASIC1b, as well as TRPV1, have biophysical properties that are indistinguishable from those of mice [14, 20]. Behavioral acid insensitivity is accounted for by a genetic variation in the voltage-gated Na + channel subunit 1.7 (NaV1.7), which confers enhanced acid inhibition [14].…”
Section: Introductionmentioning
confidence: 99%
“…We were not able to identify the paratrigeminal nucleus in the Ansell's mole‐rat, a brain area involved in the integration of somatosensory reflexes related to nociceptive, respiratory, and cardiovascular mechanisms (Caous, de Sousa Buck, & Lindsey, ). This nucleus was also not demonstrated in the naked mole‐rat (Xiao et al, ), a species for which reduced pain sensitivity has been reported (Omerbašić et al, ; Park et al, ).…”
Section: Resultsmentioning
confidence: 91%